Optimal Robot Path Planning using Enhanced Particle Swarm Optimization algorithm - Mohammed, Athraa Jasim; Ghathwan, Khalil Ibrahim; Yusof, Yuhanis (Iraqi Journal of Science, 2020)
The aim of robot path planning is to search for a safe path for the mobile robot. Even though there exist various path planning algorithms for mobile robots, yet only a few are optimized. The optimized algorithms include the Particle Swarm Optimization (PSO) that finds the optimal path with respect to avoiding the obstacles while ensuring safety. In PSO, the sub-optimal solution takes place frequently while finding a solution to the optimal path problem. This paper proposes an enhanced PSO algorithm that contains an improved particle velocity. Experimental results show that the proposed Enhanced PSO performs better than the standard PSO in terms of solution’s quality. Hence, a mobile robot implementing the proposed algorithm operates better and is more secure.